MODEL PEMASARAN DIGITAL ‘TRANSMEDIA BRANDING’ PADA CHANNEL NARASI.TV - Nesya Nesya; Juwono Tri Atmodjo (Jurnal Visi Komunikasi, 2021)
The world of marketing is moving fast and using new media to attract consumer attention is called digital marketing. Digital marketing focuses on providing space for advertising as well as embracing consumers to participate in marketing the brand. So that in digital marketing there is the term transmedia which is a marketing communication process where information about a brand is packaged in an integrated narrative that is disseminated into contributions in various media channels with the aim of creating certain experiences. This phenomenon has begun to be developed by the digital platform Narasi.Tv, a digital-based company with the www.narasi.tv page. Established in September 2017, Narasi.Tv has a number of programs that are disseminated on social media. Researchers want to see Narasi.Tv in presenting media content on its channel, advertising space on Narasi.Tv, and the transmedia branding model on Narasi.Tv as a whole. This research uses a qualitative approach with study methods collected based on the results of interviews, observations, and documentation. The result of this research is Narasi.Tv applies transmedia branding which includes narration, participation, and brand. Narasi.Tv as a media for young people to embrace its audience aged 18-35 years to be involved in uploaded content. Narasi.Tv also creates content with advertisers with the concept of collaboration where the content must contain positive values that are in line. Narasi.Tv will also not run collaboration content at any time.